P 17 Posttraumatic Headache – Pain Related Evoked Potentials (PREP) and Conditioned Pain Modulation (CPM) as possible biomarkers for identification of risk patients. (May 2022) - Jessen, J.; Özgül, Ö.; Forsting, J.; Höffken, O.; Schwenkreis, P.; Tegenthoff, M.; Enax-Krumova, E.
Abstract : Introduction : Posttraumatic headache (PTH) is one of the most common complications following traumatic brain injury (TBI)[1], though its underlying pathomechanisms have not been fully understood yet. An altered descending pain modulation seems to contribute to its development and persistence[2]. The aim of our study was to examine the pain processing in PTH-patients using pain-related evoked potentials after electrical stimulation (PREP) and conditioned pain modulation (CPM), based on their N1P1-amplitude as an objective readout. We chose a longitudinal design to analyse if PREP and CPM can be used as biomarkers for persisting PTH. Methods : We plan to recruit 30 patients with PTH and 20 healthy control subjects. Currently (October 2021) we have recruited 21 PTH-patients and 19 healthy control subjects. The patients were invited for follow-up sessions at 3 and 6 months after inclusion. The painful stimuli were applied at the dorsum of the right hand and above the right eyebrow with a concentric surface electrode while PREP were recorded over Cz and evoked pain was assessed on the numerical rating scale (NRS), as previously described [3]. For CPM we used the same electrode for painful cutaneous electric stimulation on the right hand as the test stimulus and the immersion of the left hand in a 10°C cold water bath as the conditioning stimulus. With the assessed data we calculated early and late CPM-effects for the subjective pain ratings and the objective N1-P1-amplitudes in the EEG, as recently reported[4]. Results : PTH-patients were on average 41.3 (± 10.7) years old, had a mean headache duration of 103 (± 265) weeks and a mean headache intensity of 5.9 (± 1.9) on the NRS (0-10). We currently present data at baseline. PREP parameters in both regions did not differ between PTH-patients and age-matched controls. The early CPM-effect based on PREP-amplitudes and the late CPM effect based on pain-rating were significantly less pronounced in patients than in controls. The early and late CPM effect for pain and amplitudes correlated significantly in both groups, but no significant correlation comparing CPM effects based on pain with the CPM effects based on amplitudes could be detected. Conclusions : Our preliminary results display a deficient endogenous pain modulation in PTH-patients also based on PREP-amplitude as an objective readout. The missing correlation between CPM-effects based on subjective pain ratings and PREP-amplitudes indicate different pathways involved in nociception and subjective pain perception. Further analysis of subgroups is planned after complete recruitment. References [1] Headache Classification Committee of the International Headache Society (2018) The International Classification of Headache Disorders, 3rd edition 211 [2] Jessen et al. (2021) Cephalalgia. Epub ahead of print, doi: 10.1177/03331024211030496. [3] Katsarava Z et al. (2006) Headache J Head Face Pain 46:1511–1517. [4] Höffken et al. (2017) BMC Neurol;17(1):167.